Modern aspects of surgical treatment of patients with endometrial cancer (own experience) - Movchan , O.M.; Svintsitskyі , V.S. (Medicni Perspektivi, 2022)
In recent years, endometrial cancer has taken the lead among oncological processes of the female reproductive system. The high prevalence of this disease leads to disability of the working-age population, large socio-economic losses, which determines the relevance of this problem and the search for new methods of screening, diagnostics, optimal selection of treatment, thereby affecting the quality of future life. The choice of the method of treatment of patients depends on the following main factors: age, general condition, reproductive plans of the patient, histological type of tumor, degree of its differentiation, size, localization in the uterine cavity, prevalence of the tumor process. The main treatment for endometrial cancer is surgical treatment. The principles of surgical treatment consist in the individual selection of the volume of surgical intervention, adequate lymphadenectomy, prevention of recurrence and metastases. Lymph node dissection for cancer of the uterine body has always been a controversial issue. Lymphadenectomy is necessary to accurately establish the stage of endometrial cancer. In recent years, the discussion about laparoscopic lymph node dissection in comparison with open access, to what level lymphadenectomy should be performed, how many lymph nodes, frequency of complications, prognosis of patient survival, frequency of relapses has been developing. The article highlights own vision of the role of lymphadenectomy both in laparotomy and in laparoscopy, the importance of the volume of surgical intervention and complications for each type of treatment.